Pengembangan Potensi Mahasiswa Menjadi Investor Muda di Masa Depan - Hasrun Afandi Umpu Singa (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Abstract According to Bruce Lliyd, the capital market acts as a liaison between investors and companies and government agencies through trading long-term instruments such as bonds, stocks, etc. Students as agents of change and the driving force of technological industry progress must have broad insights into financial management, and control that also pays attention to the potential for income in the form of investment. This activity aims to provide knowledge about the capital market and how to manage investments properly and correctly, to students of the Sharia Banking Department, Faculty of Economics and Islamic Business. So it is hoped that with the implementation of this seminar, students will be able to understand the capital market and how to manage investments, and can implement them in their lives in the future. Keywords: Potential Development, Young Investors, Future